Dunite powder as a green precursor in one-part alkali-activated composites: Effects on mechanical and durability properties - Benli, Ahmet; Bayraktar, Oguzhan Yavuz; Karatas, Mehmet; Bodur, Burak; Yilmazoglu, Mehmet Ugur; Kaplan, Gokhan; Bodur, Burak (Elsevier, 2025)
Natural pozzolans are a sustainable alternative to Portland cement, offering abundant alumina and reactive silica for geopolymer production. Due to their simple extraction methods, they are cost-effective and environmentally friendly. This study explores the utilization of dunite powder (DP) as a sustainable precursor in one-part alkali-activated slag-based composites (AAC), aiming to evaluate its potential to partially replace granulated blast furnace slag (GBFS). The mechanical, fresh, and durability properties of the composites were investigated by varying DP replacement levels (0%, 15%, 30%, and 60%) under an activator dosage of sodium metasilicate, with the mixtures cured at 80 degrees C for 24 h and subsequently exposed to ambient conditions. The compressive and flexural strengths were evaluated at 7, 28, and 91 days, while the fresh properties (flowability and setting time), durability under sulfate attack, high-temperature resistance, freeze-thaw resistance, dry shrinkage, sorptivity and microstructural characteristics (SEM, XRD, and FT-IR) were also examined. The compressive strength decreased with higher DP content, with the 60% DP mixture showing a 43% strength reduction at 28 days compared to the reference mixture. However, the 30% DP mixture achieved a favorable balance between strength and sustainability, demonstrating a compressive strength decrease of only 11% at 91 days. The mixture containing 15% DP demonstrated the best performance under high-temperature conditions and freeze-thaw cycles. The 60% DP mixture exhibited the highest mass and strength loss when exposed to temperatures above 400 degrees C and a 15% compressive strength reduction after 120 days of immersion in a 10% MgSO4 solution.
Keywords: Dunite Powder; Alkali-Activated Composites; Granulated Blast Furnace Slag; Sustainable Construction; Mechanical And Durability Properties